Diversity and fish distribution at Rodrigo de Freitas Lagoon, Rio de Janeiro State, Brazil, using GIS - doi: 10.4025/actascibiolsci.v36i1.18563 (Acta Scientiarum. Biological Sciences, 2013)
Fish fauna is considered a good indicator of water quality. The Rodrigo de Freitas Lagoon is located in Rio de Janeiro city with a great scenic beauty. However, along the years, the Lagoon has been negatively impacted by human activities which can be seen in massive fish deaths and blooms of toxic algae. This study evaluated fish abundance and diversity in two historical periods, and between areas of capture. Multivariate data analyses were performed to find similar groups of fish fauna and to evaluate fish abundance and their seasonal and spatial variation. It was also used the algebraic language as a tool to combine raster layers as dissolved oxygen in surface, bathymetry and fish abundance by using rules and conditions involved in the fish zoning. The zone 2, located in the south-central area of the Lagoon, had the greatest number of species and higher values of dissolved oxygen. Mollies and menhaden had high abundance and occurred in all areas. There was a marked decrease in fish diversity and abundance in the second period. The results showed that surface dissolved oxygen and salinity were identified as important factors influencing the distribution and abundance of the main fish species at the Lagoon.